2017
DOI: 10.1245/s10434-017-5894-3
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Sexual Function After Breast Cancer Surgery

Abstract: Baseline sexual dysfunction exists in women diagnosed with breast cancer. Surgery negatively impacts sexual function. Patients who choose mastectomy do not exhibit superior sexual function over those having BCS at 13 months following surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…When asked if body image was as expected, 49% said yes, 31% said that it was worse than expected and 23% said that it was better than expected 30 . Similarly, in studies examining sexuality, there was no difference in score between the CPM and no‐CPM groups 19,22 . In an interview study, women reported feeling emotionally closer to partners after the surgery compared to before the surgery, however sexually more distant, with chest numbness related to CPM to be a major factor (no comparison group) 16 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When asked if body image was as expected, 49% said yes, 31% said that it was worse than expected and 23% said that it was better than expected 30 . Similarly, in studies examining sexuality, there was no difference in score between the CPM and no‐CPM groups 19,22 . In an interview study, women reported feeling emotionally closer to partners after the surgery compared to before the surgery, however sexually more distant, with chest numbness related to CPM to be a major factor (no comparison group) 16 …”
Section: Resultsmentioning
confidence: 98%
“…A total of 81 abstracts met eligibility criteria; 81 full‐text articles were reviewed, 63 were subsequently found to be ineligible, and one article was added following review of reference lists of eligible studies. A total of 19 studies were eligible for inclusion in the analysis 7,14‐32 …”
Section: Resultsmentioning
confidence: 99%
“…In relation to sexuality, there are a variety of complaints. Dyspareunia, lack of vaginal lubrication, hypoactive desire and loss of breast tenderness have been reported as consequences of breast cancer treatment 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…These baseline data are critical for breast cancer patients because the median age at diagnosis is 62 years, 5 and many postmenopausal patients may already be experiencing some type of sexual decline at the time of diagnosis. 6 This recent article by Gass et al should encourage surgeons to reconsider their willingness to discuss with their patients the sexual side effects resulting from surgery and their approach to the discussion.…”
mentioning
confidence: 99%
“…6 Recognizing that women desire sex after treatment, we should try to protect and preserve sexual function. Gass et al showed that surgery affects function.…”
mentioning
confidence: 99%